A computational docking study on the pH dependence of peptide binding to HLA-B27 sub-types differentially associated with ankylosing spondylitis - ÖZBEK SARICA, PEMRA (SPRINGER, 2016)
A single amino acid difference (Asp116His), having a key role in a pathogenesis pathway, distinguishes HLA-B*27:05 and HLA-B*27:09 sub-types as associated and non-associated with ankylosing spondylitis, respectively. In this study, molecular docking simulations were carried out with the aim of comprehending the differences in the binding behavior of both alleles at varying pH conditions. A library of modeled peptides was formed upon single point mutations aiming to address the effect of 20 naturally occurring amino acids at the binding core peptide positions. For both alleles, computational docking was applied using Autodock 4.2. Obtained free energies of binding (FEB) were compared within the peptide library and between the alleles at varying pH conditions. The amino acid preferences of each position were studied enlightening the role of each on binding. The preferred amino acids for each position of pVIPR were found to be harmonious with experimental studies. Our results indicate that, as the pH is lowered, the capacity of HLA-B*27:05 to bind peptides in the library is largely lost. Hydrogen bonding analysis suggests that the interaction between the main anchor positions of pVIPR and their respective binding pocket residues are affected from the pH the most, causing an overall shift in the FEB profiles.
Keywords: Computational molecular docking; Autodock 4.2; HLA docking; Peptide docking; HLA-B27; pH change; Cross-presentation; MHC CLASS-I; HISTOCOMPATIBILITY COMPLEX-MOLECULES; CONTROLS PHAGOSOMAL PH; HLA CLASS-I; CROSS-PRESENTATION; DENDRITIC CELLS; EXOGENOUS ANTIGEN; SELF-PEPTIDE; PREDICTION; PROTEINS